Evaluation of serum folate, vitamin B12 and homocysteine among blood donors in Lagos State University teaching hospital, Lagos, Nigeria - Uche, Ebele I.; Akinbami, Akinsegun A.; Bamiro, Rafautu; Adeyemi, Ibukun O.; Ibrahim, Nda (International Journal of Scientific Reports, 2022)
Background: Folate, vitamin B12 deficiency and hyperhomocysteinaemia have been reported as important risk factors for the development of cardiovascular events and ischaemic stroke. These vitamin deficiencies are also implicated in the pathogenesis of several diseases like anaemia, dementia, Alzheimer’s disease and cancers. This study determined the serum levels of vitamins B12, folate, and homocysteine among blood donors in the Lagos State University Teaching Hospital, Ikeja, Lagos, Nigeria. Methods: This was a descriptive, cross-sectional study done among blood donors at the donor clinic of LASUTH Ikeja, Lagos, Nigeria. One hundred blood donors who met the donor inclusion criteria of LASUTH were recruited consecutively into the study. Five ml of venous blood was collected from each consenting participant into ethylene Diamine Tetra-acetic Acid (EDTA) and plain bottles for the determination of full blood count and folate, vitamin B12/homocysteine respectively. Data were analyzed with statistical package for social science version 23.0, the p value was set at ≤0.05. Results: The mean age of the study participants was 33.36±8.31 years. The mean serum homocysteine, folate and VitB12 levels among the study participants were 5.59±9.14 nmol/l, 21.57±4.15ng/ml and 1694.38±592.83 pg/ml respectively. About 8% of the study participants had serum homocysteine levels more than 15nmol/L, 4% had vitamin B12 levels less than 203pg/ml while all 100 participants had normal folate levels of 4ng/ml and above. Conclusions: The prevalence of hyperhomocysteinemia, vitaminB12 and folate deficiencies among blood donors in LASUTH is low.